High performance polymers. (Thousand Oaks, Calif. Sage Publications, 1989)
In a field of rapid innovation the journal accepts articles on research in high performance polymer science and technology, from molecular modelling and polymer design to the testing and performance of the polymers in the target applications.
UP System perpetual contents: 2019
Keywords: Polymerization -- Periodicals; Polymers -- Periodicals